The use of Inverse Neural Networks in the Fast Design of Printed Lens Antennas - Gosal, Gurpreet Singh (Université d'Ottawa / University of Ottawa, 2015)
In this thesis the major objective is the implementation of the inverse neural network concept in the design of printed lens (transmitarray) antenna. As it is computationally extensive to perform full-wave simulations for entire transmitarray structure and thereafter perform optimization, the idea is to generate a design database assuming that a unit cell of the transmitarray is situated inside a 2D infinite periodic structure. This way we generate a design database of transmission coefficient by varying the unit cell parameters. Since, for the actual design, we need dimensions for each cell on the transmitarray aperture and to do this we need to invert the design database. The major contribution of this thesis is the proposal and the implementation of database inversion methodology namely inverse neural network modelling. We provide the algorithms for carrying out the inversion process as well as provide check results to demonstrate the reliability of the proposed methodology. Finally, we apply this approach to design a transmitarray antenna, and measure its performance.
Keywords: ANN (Artificial Neural Network); INN (Inverse Neural Network); Forward neural network; Design database; S-parameter database; Printed Lens; Transmitarray; Engineered Surfaces; Inversion; Oblique Incidence; Unit cell; Training data; Test data; Neural network learning; Electric field; Polarization; Transmission coefficient; Transmission phase; Transmission amplitude; Incidence angle; Feed; Aperture